Racially Writing the Republic : Racists, Race Rebels, and Transformations of American Identity - Harris, Duchess; Baum, Bruce David, 1960- (Book collections on Project MUSE., 2009)
Investigates the history of U.S. political thought, dreams, and national identity by foregrounding the debasing role of race and racialized identities in constructions and transformations of what it has meant to be American.